Bioactivities of triterpenes and a sterol from Syzygium samarangense - Raga, Dennis D. (Animo Repository, 2011)
Cycloartenyl stearate (1a), lupenyl stearate (1b), sitosteryl stearate (1c), and 24-methylenecycloartanyl stearate (1d) (sample 1) from the air-dried leaves of Syzygium samarangense exhibited potent analgesic and anti-infl ammatory activities at effective doses of 6.25 mg/kg body weight and 12.5 mg/kg body weight, respectively. Sample 1 also exhibited negligible toxicity on zebrafi sh embryonic tissues. There were incidences of mortality upon direct exposure of sample 1 to dechorionated embryos, but higher mortality and aberration were observed during intact chorion treatment. © 2011 Verlag der Zeitschrift für Naturforschung, Tübingen.